Continuing education as an agent for professional improvement and competitiveness in Mexico (Revista Electrónica Calidad en la Educación Superior, 2022)
Continuing education has now been characterized by a fairly wide educational offer in the international concert in the form of courses, workshops and diplomas, among other modalities, mainly delivered by higher education institutions. Notwithstanding the important role this activity plays for society, within the framework of globalization, still has challenges that reside in accreditation, adequacy to new means of communication and circumvent language limits. Nevertheless, continuing education is one of the ways to empower and improve professional practice in Mexico. In this contribution we show what continued education, its relevance and the challenges it will face in Mexico.
Keywords: education permanen; education; permanent education; distance education; adult education; workers education